Measuring the Complex Construct of Macroergonomic Compatibility: A Manufacturing System Case Study - Arturo Realyvásquez; Aide A. Maldonado-Macías (Complexity)
Macroergonomic compatibility (MC) refers to the extent to which macroergonomic factors and elements (MFEs) interact positively with humans. It is one of the most complex constructs to measure in work systems and in ergonomics. The goal of this paper is to determine the levels of MC in a manufacturing system. As methods, we use the macroergonomic compatibility index (MCI) and the Macroergonomic Compatibility Questionnaire (MCQ). The MCQ was administered in its three versions (i.e., worker version, expert version, and medical department version) to collect data about the macroergonomic practices implemented in the manufacturing company. Regarding results, all the macroergonomic factors and most of the macroergonomic elements showed a low level of MC; that is, MCI < 0.7. Only macroergonomic elements Education, Knowledge, and Skills reached a medium level; namely, MCI = 0.709. The factor with the highest level of MC was the Person factor (MCI = 0.328). Similarly, the whole manufacturing system showed a low level of MC. In conclusion, the studied manufacturing company requires urgent macroergonomic interventions. Also, we found that the MCI can effectively measure the level of MC of MFEs and can guide the implementation of macroergonomic practices (MPs) and explain the MC construct.